Ultrasensitive broadband photodetectors based on two-dimensional Bi2O2Te films - Tian, Pin; Wu, Hongbo; Tang, Libin; Xiang, Jinzhong; Ji, Rongbin; Lau, Shu Ping; Teng, Kar Seng; Guo, Wei; Yao, Yugui; Lain-Jong, Li (Journal of materials chemistry. C, Materials for optical and electronic devices, 2021)
Two-dimensional (2D) materials exhibit many unique optical and electronic properties that are highly desirable for application in optoelectronics. Here, we report the study of a photodetector based on 2D Bi2O2Te grown on an n-Si substrate. The 2D Bi2O2Te material was transformed from a sputtered Bi2Te3 ultrathin film after rapid annealing at 400 °C for 10 min under an air atmosphere. The photodetector was capable of detecting a broad wavelength ranging from 210 nm to 2.4 μm with an excellent responsivity of up to 3 × 105 and 2 × 104 AW−1 and a detectivity of 4 × 1015 and 2 × 1014 Jones for deep ultraviolet (UV) and short-wave infrared (SWIR) under weak light illumination, respectively. The effectiveness of 2D materials in weak light detection was investigated by the analysis of the photocurrent density contribution. Importantly, the facile growth process at low annealing temperatures would allow the direct large-scale integration of 2D Bi2O2Te materials with the complementary metal–oxide–semiconductor (CMOS) technology.